2020
DOI: 10.1007/s00428-020-02930-5
|View full text |Cite
|
Sign up to set email alerts
|

Stromal categorization in early oral tongue cancer

Abstract: Stromal categorization has been used to classify many epithelial cancer types. We assessed the desmoplastic reaction and compared its significance with other stromal characteristics in early (cT1-2N0) oral tongue squamous cell carcinoma (OTSCC). In this multi-institutional study, we included 308 cases treated for early OTSCC at five Finnish university hospitals or at the A.C. Camargo Cancer Center in São Paulo, Brazil. The desmoplastic reaction was classified as immature, intermediate, or mature based on the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 38 publications
2
15
0
Order By: Relevance
“…Currently, some studies examine DR and TIL considering the distribution of tumors nest and stroma; DR and TILs are assessed as the concepts of “tumor-stroma ratio” and “Immune phenotype,” respectively [ 47 , 48 ]. Stroma-rich OSCC with low infiltration of lymphocytes has an aggressive behavior and is associated with unfavorable prognosis [ 49 ], which was consistent with our result, in which DR-I and TILs-L were significantly associated with powerful prognostic factor ENE + .”…”
Section: Discussionsupporting
confidence: 91%
“…Currently, some studies examine DR and TIL considering the distribution of tumors nest and stroma; DR and TILs are assessed as the concepts of “tumor-stroma ratio” and “Immune phenotype,” respectively [ 47 , 48 ]. Stroma-rich OSCC with low infiltration of lymphocytes has an aggressive behavior and is associated with unfavorable prognosis [ 49 ], which was consistent with our result, in which DR-I and TILs-L were significantly associated with powerful prognostic factor ENE + .”…”
Section: Discussionsupporting
confidence: 91%
“…At the same time, some of the relevant studies analyzed stromal‐related histopathologic markers including stromal infiltrating lymphocytes (one study) 18 and tumor–stroma ratio (TSR; three studies) 17,40,41 which were significantly associated with prognosis. However, other stromal markers (including desmoplastic reaction in one study, 2 lymphocytic host response in two studies, 13,42 and muscular invasion in three studies 43–45 ) were reported in the relevant studies and the findings were not suggestive of prognostic relevance. Among these emerging histologic markers, two cancer‐related markers (tumor budding and WPOI) in addition to only one stromal‐related marker (TSR) were repeatedly reported (Table 1).…”
Section: Resultsmentioning
confidence: 88%
“…Oral tongue squamous cell carcinoma (OTSCC) is the most common cancer occurring in the oral cavity 1 . OTSCC is considered an aggressive malignancy with a poorer prognosis than SCC of the other locations of the oral cavity 2 . The incidence of OTSCC increases with age; however, the incidence in young patients under the age of 40 has reported to be increasing 3 .…”
Section: Introductionmentioning
confidence: 99%
“…proposed a histo-score based on the assessment of the lymphocytic infiltrate and tumor differentiation, and showed that the score gave a good prediction of survival in oral tongue cancer ( 14 ). Our group ( 15 ) proposed stromal classification, based on the assessment of tumor-infiltrating lymphocytes and tumor-stroma ratio, with a promising prognostic value in early oral tongue cancer.…”
Section: Assessment Of Immune Response As a Part Of Grading Systems Omentioning
confidence: 99%
“…Accumulating evidence has shown the significance of this method in various cancers ( 17 19 ). In OSCC, our group ( 15 ) has recently reported that the assessment of stromal TILs [as proposed by TILs Working Group ( 9 )] can be used as a significant prognostic tool for the prediction of overall survival, disease-specific survival and disease-free survival in a large multicenter cohort of early oral tongue cancer. This assessment method has also been used successfully for other subsites of head and neck cancers ( 16 ).…”
Section: Histologic Semiquantitative Assessment Of Tumor-infiltratingmentioning
confidence: 99%